2016
DOI: 10.1016/j.agwat.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential risks associated with chemicals in wastewater used for irrigation in arid and semiarid zones: A review

Abstract: 10Irrigation with raw, partially and treated wastewater is a widespread practice in many 11 arid and semi-arid zones. The importance of wastewater for agriculture has 12 increasingly been recognised not only as a valuable water resource but also for its 13 nutrient value. However, inappropriate management of irrigation with wastewater can 14 pose substantial risks to public health and the surrounding environment as a result of 15 its microbial and toxic components. In this review, we summarise recent research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(111 citation statements)
references
References 96 publications
2
95
0
14
Order By: Relevance
“…Market proximity, high opportunities for income generation, reliable and free irrigation water supply, and minimum artificial fertilizer requirement are the often cited benefits of irrigation within cities (Drechsel et al 2006;Qadir et al 2010). However, long-term application of partially treated or untreated wastewater could result in accumulation of heavy metals in the soil (Elgallal et al 2016). Effluents from household and industries, drainage water, atmospheric deposition, and trafficrelated emissions transported with storm water into the sewage and/or irrigation system carry number of pollutants and enrich the urban waste water with heavy metals (Saha et al 2015;Zia et al 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…Market proximity, high opportunities for income generation, reliable and free irrigation water supply, and minimum artificial fertilizer requirement are the often cited benefits of irrigation within cities (Drechsel et al 2006;Qadir et al 2010). However, long-term application of partially treated or untreated wastewater could result in accumulation of heavy metals in the soil (Elgallal et al 2016). Effluents from household and industries, drainage water, atmospheric deposition, and trafficrelated emissions transported with storm water into the sewage and/or irrigation system carry number of pollutants and enrich the urban waste water with heavy metals (Saha et al 2015;Zia et al 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…Although TSE is certainly an option for agriculture, many concerns exist as to its safety and social acceptability, particularly the accumulation of heavy metals that are toxic to humans and animals, as well as the potential to transmit pathogenic micro-organisms [9][10][11][12]. TSE typically has higher salt (200-3000 mg/L TDS), nutrient, solids and frequently metal content than conventional irrigation water [13][14][15][16] and it has been observed that these metals can accumulate in food crops. For example, a recent study in which TSE was used to grow okra in Saudi Arabia found that the okra frequently accumulated Ni, Pb, Cd and Cr above safe limits and the authors concluded that the vegetable was not safe for direct consumption by human beings [17].…”
Section: Treated Sewage Effluent (Tse)mentioning
confidence: 99%
“…One of the relevant aspects, of a sanitary nature, is related to the recommended microbiological guidelines for the use of sewage in agriculture (Pedrero et al, 2012;US EPA, 2012), where concerns are concentrated on the health of the farmer and consumers of agricultural products. Other environmental aspects refer to the possible accumulation of heavy metals and toxic elements in soils and plants, the contamination of groundwater by these substances and nitrate (Elgallal et al, 2016;Leal et al, 2009), increase in soil salinity and sodicity (Matsumoto et al, 2012;Ganjegunte et al, 2017;Assouline & Narkis, 2011;Muyen et al, 2011) changes in its physical properties (Abegunrin et al, 2016;Bonini et al, 2014;Levy et al, 2014), and unbalanced supply of nutrients to plants (Blum, 2011;Pereira et al, 2011). Table beet consumption, as part of a healthy diet, is intensified in the summer, a time of low supply by producers due to high temperatures and precipitation.…”
Section: Introductionmentioning
confidence: 99%